Pemaknaan Puisi “Jarak 1” Karya Heri Isnaini Dengan Pendekatan Hermeneutika - Syawalia Fazarizqa Nurhidayat (LPPM Politeknik Pratama, 2023)
Poetry is an imaginative literary work, which is composed through words but is not easily understood by readers because everyone has their own point of view and does not have the knowledge to analyze poetry. The purpose of this study is to analyze poetry with a hermeneutic approach. The method used in this study is a qualitative method by describing the content by analyzing poetry using a hermeneutic approach. Hermeneutics is a very scientific and well-studied approach to poetry. Because the hermeneutic approach to poetry is based on our interpretation as researchers of structured poetry. The stages carried out in this discussion begin with analyzing the array, analyzing the structure that composes the text of the poem, objectifying the structure of the text, and interpreting the text of the poem. Thus, the results of this study can show the hidden meaning in the poem